1991
DOI: 10.1002/ijc.2910490411
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a breast cancer screening programme on quality‐adjusted life‐years

Abstract: Trials have shown that breast cancer screening is effective in reducing breast cancer mortality and gaining life-years. The question is whether taking into account the impact of a screening programme on quality of life would lead to a less positive view. Screening may have effects on quality of life in the short run for women participating and effects in the long run as a result of the expected shift in the number of women experiencing early and advanced phases of the disease, after the initiation of the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 18 publications
4
98
2
1
Order By: Relevance
“…However, our sensitivity analysis showed that adjusting for quality of life has little impact on cost-effectiveness estimates, which is in line with earlier findings. 41,50 In addition, when we adjust for quality of life, the incremental cost-effectiveness ratios are slightly more favourable and therefore remain below the threshold of £20,000 per QALY gained (approximately e24,000 per QALY gained). When we compare the ICERs to the willingness-to-pay threshold of e20,000 per QALY gained, often cited in Dutch cost-effectiveness analyses, [51][52][53] all screening scenarios remain cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our sensitivity analysis showed that adjusting for quality of life has little impact on cost-effectiveness estimates, which is in line with earlier findings. 41,50 In addition, when we adjust for quality of life, the incremental cost-effectiveness ratios are slightly more favourable and therefore remain below the threshold of £20,000 per QALY gained (approximately e24,000 per QALY gained). When we compare the ICERs to the willingness-to-pay threshold of e20,000 per QALY gained, often cited in Dutch cost-effectiveness analyses, [51][52][53] all screening scenarios remain cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…3 The number of consultations after recall in the presence of screening is calculated by using the number of screen-detected cancers and a positive predictive value (PPV) of 30% 30 (ages 50-74) or 12% (ages [40][41][42][43][44][45][46][47][48][49]. The number of consultations after recall in the absence of screening is calculated by using the number of clinically detected cancers and a PPV of 58.3%.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were identified that reported costs per quality-adjusted year of life saved. It has recently been estimated that quality adjustment reduces the estimated effec tiveness of a breast cancer screening program by about 8%, which is considered too small an effect to influence decision-making (26). Studies were included in the review only if costs per year of life saved were reported; costs were defined to include screening costs, the costs associated with the diagnostic work-up of false-positives, and the savings in treatment costs; and both costs and benefits occurring in the future were discounted to reflect societal time preference .…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…This is 17 The 2010 systematic review of the utility losses from breast cancer included estimates of this loss of between 11% and 34% 15 but warned that the studies could not be synthesised.…”
Section: Strengths and Limitationsmentioning
confidence: 99%